2018
DOI: 10.3390/molecules23123081
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Analysis to Detect Reduced Bone Quality after Sciatic Neurectomy in Mice

Abstract: Bone mineral density (BMD) is a commonly used diagnostic indicator for bone fracture risk in osteoporosis. Along with low BMD, bone fragility accounts for reduced bone quality in addition to low BMD, but there is no diagnostic method to directly assess the bone quality. In this study, we investigated changes in bone quality using the Raman spectroscopic technique. Sciatic neurectomy (NX) was performed in male C57/BL6J mice (NX group) as a model of disuse osteoporosis, and sham surgery was used as an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…S8F). Both spectral regions are characteristic of the organic matrix ( 31 ), and this ratio has previously been used to estimate the amount of total organic molecule content relative to matrix proteins ( 32 ). Modified values of the CH 2 -wag band have also been observed in some types of malignant tissues ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…S8F). Both spectral regions are characteristic of the organic matrix ( 31 ), and this ratio has previously been used to estimate the amount of total organic molecule content relative to matrix proteins ( 32 ). Modified values of the CH 2 -wag band have also been observed in some types of malignant tissues ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The skin incision was made posterior to the femoral trochanteric region. The sciatic nerve was exposed and a 1-cm-long segment was resected before the EA treatment, as described in Ishimaru et al 20 . In the sham group mice were anesthetized and incised in the same manner as the sciatic neurectomy group but without sciatic neurectomy.…”
Section: Methodsmentioning
confidence: 99%
“…In both reference spectra, the peaks attributed to amide III of β-sheet/random coils, α-helix, α-fibrous/γ(CH 2), and α-helix were detected at 1,230 44) , 1,264 44) , 1,312 45,46) , and 1,340 cm −1 44) , respectively. In addition, the peaks assigned to δ(C-C), amide II, and amino acids (tyrosine and phenylalanine) were observed at 1,450 [44][45][46][47] and 1,605 cm −1 45,46) , respectively. In the region of amide I, the peaks attributed to α-helix and random coils were observed at 1,650 and 1,677 cm −1 45,46) , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4-6). The peak intensity ratios for 1,264 44) and 1,312 cm −1 45) (α-helix and α-fibrous/γ(CH2)) or for 1,605 and 1,650 cm −1 (amino acid and α-helix) 45) (Table 3) indicated that BSA may have actually adsorbed onto both c-OCP and w-OCP. Although the BSA adsorption sites on c-OCP and w-OCP surfaces are unclear, the mechanism may involve some types of adsorption [56][57][58] .…”
Section: Discussionmentioning
confidence: 99%